TRANSFORMING THROUGH NEP2020: A VISION FOR SKILL-BASED EXPERIENTIAL LEARNING - Sharma, Divyangna; Jain, Vinod Kumar (International Journal of Research -GRANTHAALAYAH, 2025)
In today’s rapidly evolving world, skill development has become an essential requirement for individuals of all ages and professions. Skills are the foundation of innovation and progress, and their enhancement fosters new ways of thinking, leading to the generation of creative ideas. The National Education Policy (NEP) 2020 envisions a future-ready generation equipped with diverse skills to meet emerging challenges and opportunities. Skills such as computer programming, problem-solving, self-management, and communication are crucial in this context. Computer skills enhance typing, graphic design, and video creation abilities. Problem-solving skills nurture logical and analytical thinking. Self-management, closely linked with time management, promotes discipline and punctuality. Communication skills foster confidence, which is integral to holistic personality development. Skill development, therefore, is vital for every generation. Humans are inherently innovative, and education must nurture this potential. NEP 2020 plays a transformative role by embedding skill-based, experiential learning into the education system, paving the way for creative and critical thinkers. The policy introduces significant reforms aimed at equipping students with practical skills applicable in real-life situations. This study explores the skill-building suggestions outlined in NEP 2020 and discusses effective strategies for their implementation, emphasizing the policy's role in shaping a skilled, confident, and innovative generation prepared for the future.